Performance evaluation of four rapid antigen tests for the detection of Respiratory syncytial virus. Issue 10 (28th March 2016) - Jung, Bo Kyeung; Choi, Sung Hyuk; Lee, Jong Han; Lee, JungHwa; Lim, Chae Seung
Abstract : Rapid identification of Respiratory syncytial virus (RSV) is important in the management of infected patients. Rapid diagnostic tests (RDT) are widely used for this purpose. This study aimed to evaluate the clinical performance of four RSV antigen tests including the BinaxNow RSV Card test, SD Bioline RSV test, BD Veritor RSV test, and Humasis RSV antigen test in comparison with real‐time RT–PCR as the reference method. Nasopharyngeal swabs were collected from 280 patients with symptoms of lower respiratory tract infection and stored at −80°C. All swabs were tested for RSV using four rapid antigen tests and real time RT–PCR. The sensitivity of the BinaxNow RSV Card test, SD Bioline RSV test, BD Veritor RSV test, and Humasis RSV Antigen tests were 62.5%, 61.3%, 65.0%, and 67.5% for RSV A, and 61.3%, 65.0%, 61.3%, and 67.5% for RSV B compared to real time RT–PCR, respectively. The specificity of BD Veritor RSV test was 95.8% and those of the other three RDTs was 100%. Commercial RSV antigen detection assays are useful tools for the rapid diagnosis of RSV infection. However, confirmatory testing is always recommended. J. Med. Virol. 88:1720–1724, 2016 . © 2016 Wiley Periodicals, Inc.